LO15: Paramedic and allied health professional interventions at long-term care facilities to reduce emergency department visits: systematic review. (May 2020) - Leduc, S.; Cantor, Z.; Kelly, P.; Thiruganasambandamoorthy, V.; Wells, G.; Vaillancourt, C.
Abstract : Introduction: Emergency department (ED) crowding, long waits for care, and paramedic offload delay are of increasing concern. Older adults living in long-term care (LTC) are more likely to utilize the ED and are vulnerable to adverse events. We sought to identify existing programs that seek to avoid ED visits from LTC facilities where allied health professionals are the primary providers of the intervention and, to evaluate their efficacy and safety. Methods: We completed this systematic review based on a protocol we published apriori and following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. We systematically searched Medline, CINAHL and EMBASE with terms relating to long-term care, emergency services, hospitalization and allied health personnel. Two investigators independently selected studies and extracted data using a piloted standardized form and evaluated the risk of bias of included studies. We report a narrative synthesis grouped by intervention categories. Results: We reviewed 11, 176 abstracts and included 22 studies. Most studies were observational and few assessed patient safety. We found five categories of interventions including: 1) use of advanced practice nursing; 2) a program called Interventions to Reduce Acute Care Transfers (INTERACT); 3) end-of-life care; 4) condition specific interventions; and 5) use of extended care paramedics. Of the 13 studies that reported ED visits, all (100%) reported a decrease, and of the 16/17 that reported hospitalization, 94.1% reported a decrease. Patient adverse events such as functional status and relapse were seldom reported (6/22) as were measures of emergency system function such as crowding/inability of paramedics to transfer care to the ED (1/22). Only 4/22 studies evaluated patient mortality and 3/4 found a non-statistically significant worsening. When measured, studies reported decreased hospital length of stay, more time spent with patients by allied health professionals and cost savings. Conclusion: We found five types of programs/interventions which all demonstrated a decrease in ED visits or hospitalization. Many identified programs focused on improved primary care for patients. Interventions addressing acute care issues such as those provided by community paramedics, patient preferences, and quality of life indicators all deserve more study.